Adverse perinatal events, treatment gap, and positive family history linked to the high burden of active convulsive epilepsy in Uganda: A population‐based study. Issue 2 (13th March 2017) - Kakooza‐Mwesige, Angelina; Ndyomugyenyi, Donald; Pariyo, George; Peterson, Stefan Swartling; Waiswa, Paul Michael; Galiwango, Edward; Chengo, Eddie; Odhiambo, Rachael; Ssewanyana, Derrick; Bottomley, Christian; Ngugi, Anthony K.; Newton, Charles R. J. C.; et al.
Summary: Objective: To determine the prevalence of active convulsive epilepsy (ACE) and describe the clinical characteristics and associated factors among a rural Ugandan population. Methods: The entire population in Iganga/Mayuge Health Demographic Surveillance Site (IM‐HDSS) was screened using two questions about seizures during a door‐to‐door census exercise. Those who screened positive were assessed by a clinician to confirm diagnosis of epilepsy. A case control study with the patients diagnosed with ACE as the cases and age/sex‐matched controls in a ratio of 1:1 was conducted. Results: A total of 64, 172 (92.8%) IM‐HDSS residents, with a median age of 15.0 years (interquartile range [IQR]: 8.0–29.0), were screened for epilepsy. There were 152 confirmed ACE cases, with a prevalence of 10.3/1, 000 (95% confidence interval [CI]: 9.5–11.1) adjusted for nonresponse and screening sensitivity. Prevalence declined with age, with the highest prevalence in the 0–5 years age group. In an analysis of n = 241 that included cases not identified in the survey, nearly 70% were unaware of their diagnosis. Seizures were mostly of focal onset in 193 (80%), with poor electroencephalogram (EEG) agreement with seizure semiology. Antiepileptic drug use was rare, noted in 21.2% (95% CI: 16.5–25.8), and 119 (49.3%) reported using traditional medicines. History of an abnormal antenatal period (adjusted odds ratio [aOR] 10.28; 95%CI 1.26–83.45; p = 0.029) and difficulties in feeding, crying, breathing in the perinatal period (aOR 10.07; 95%CI 1.24–81.97; p = 0.031) were associated with ACE in children. In adults a family history of epilepsy (aOR 4.38 95%CI 1.77–10.81; p = 0.001) was the only factor associated with ACE. Significance: There is a considerable burden of epilepsy, low awareness, and a large treatment gap in this population of rural sub‐Saharan Africa. The identification of adverse perinatal events as a risk factor for developing epilepsy in children suggests that epilepsy burden may be decreased by improving obstetric and postnatal care.